Fic Proteins of Campylobacter fetus subsp. venerealis Form a Network of Functional Toxin–Antitoxin Systems - Sprenger, Hanna; Kienesberger, Sabine; Pertschy, Brigitte; Pöltl, Lisa; Konrad, Bettina; Bhutada, Priya; Vorkapic, Dina; Atzmüller, Denise; Feist, Florian; Högenauer, Christoph; Gorkiewicz, Gregor; Zechner, Ellen L. (Frontiers in Microbiology, 2017)
Enzymes containing the FIC (filamentation induced by cyclic AMP) domain catalyze post-translational modifications of target proteins. In bacteria the activity of some Fic proteins resembles classical toxin-antitoxin (TA) systems. An excess of toxin over neutralizing antitoxin can enable bacteria to survive some stress conditions by slowing metabolic processes and promoting dormancy. The cell can return to normal growth when sufficient antitoxin is present to block toxin activity. Fic genes of the human and animal pathogen Campylobacter fetus are significantly associated with just one subspecies, which is specifically adapted to the urogenital tract. Here we demonstrate that the fic genes of virulent isolate C. fetus subsp. venerealis 84-112 form multiple TA systems. Expression of the toxins in E. coli caused filamentation and growth inhibition phenotypes reversible by concomitant antitoxin expression. Key active site residues involved in adenylylation by Fic proteins are conserved in Fic1, Fic3 and Fic4, but degenerated in Fic2. We show that both Fic3 and the non-canonical Fic2 disrupt assembly and function of E. coli ribosomes when expressed independently of a trans-acting antitoxin. Toxicity of the Fic proteins is controlled by different mechanisms. The first involves intramolecular regulation by an inhibitory helix typical for Fic proteins. The second is an unusual neutralization by heterologous Fic-Fic protein interactions. Moreover, a small interacting antitoxin called Fic inhibitory protein 3, which appears unrelated to known Fic antitoxins, has the novel capacity to bind and neutralize Fic toxins encoded in cis and at distant sites. These findings reveal a remarkable system of functional crosstalk occurring between Fic proteins expressed from chromosomal and extrachromosomal modules. Conservation of fic genes in other bacteria that either inhabit or establish pathology in the urogenital tract of humans and animals underscores the significance of these factors for niche-specific adaptation and virulence.